2020
DOI: 10.3390/ani10050837
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Lactobacillus spp., Enrofloxacin or Doxycycline Negatively Affects the Viability of Mycoplasma bovis in Diluted Bovine Semen

Abstract: Mycoplasma bovis is an important etiologic agent of bovine mycoplasmosis in cattle. Different transmission routes have been described, including those related to reproduction. The presence of mycoplasma in semen has led to its appearance in infection-free areas through artificial insemination (AI). Semen was recently reported to be the initial source of two M. bovis mastitis outbreaks in two closed dairy herds in Finland. This questions the effectiveness of the antimicrobials currently used in semen extenders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…For instance, the acidification to pH 4 during 1 h was enough to eliminate viable M. bovis organisms in milk [23]. We also found out that the viability of M. bovis was negatively affected by the addition of L2 in diluted bull semen which coincided with a significant decrease of pH after 15 h in incubation [25]. Other authors observed a harmful effect on Mycoplasma agalactiae and Mycoplasma mycoides subsp.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…For instance, the acidification to pH 4 during 1 h was enough to eliminate viable M. bovis organisms in milk [23]. We also found out that the viability of M. bovis was negatively affected by the addition of L2 in diluted bull semen which coincided with a significant decrease of pH after 15 h in incubation [25]. Other authors observed a harmful effect on Mycoplasma agalactiae and Mycoplasma mycoides subsp.…”
Section: Discussionsupporting
confidence: 51%
“…An inoculum of M. bovis (1 × 10 9 CFU/mL) and two inoculums of Lactobacillus spp., L1 (3.24 × 10 6 CFU/mL) and L2 (3.24 × 10 8 CFU/mL) were prepared in a modified broth SP4 as previously described [25]. The reference strain PG45, and the lyophilized commercial probiotic, NS Femibiotic®, based on a mix of Lactobacillus crispatus, Lactobacillus gasseri and Lactobacillus brevis, were employed for preparing the inoculums of M. bovis and L1 and L2 respectively.…”
Section: Preparation Of the M Bovis And Lactobacillus Spp Inoculumsmentioning
confidence: 99%
See 3 more Smart Citations